Manusia Sebagai Subyek Hukum - Gilang Rizki Aji Putra (ADALAH, 2020)
As a party who can act in law, legal subjects have the authority law that is not owned by the other party. There are two categories of legal subjects, namely human and legal subjects legal entities. Humans as legal subjects are natural. Whose question man so that he can become a subject of law, cannot be answered only by one sentence. The human essence is one of the basics to answer it. Question The next thing is what is a legal entity so that he can be domiciled as a legal entity? legal entity. These are the questions that this paper will answer.